APPLICATION OF HYDROLYSIS PRODUCTS IN THE PRODUCTION OF ORGANIC BINDERS - Makhammatov Muzaffar Safarovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
With increasing volumes of road construction, it is necessary to expand the range of organic binders, which provide a significant economic effect through the use of cheap raw materials, improving working conditions, and in some cases, even for the use of local stone materials instead of crushed ones.